TEACHING PROCESSES AND LEARNING STYLES - Tulkinova Durdonakhon; Gaforov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The teaching process and learning styles are complex and multifaceted concepts that involve various factors, including individual preferences, cognitive abilities, and educational environments. Teaching is fundamentally a process, including planning, implementation, evaluation, and revision. Planning and teaching a class are familiar ideas to most instructors. More overlooked are the steps of evaluation and revision.